2017
DOI: 10.1002/tee.22403
|View full text |Cite
|
Sign up to set email alerts
|

Motion characteristics of a charged metal particle in insulating oil under flow state

Abstract: Problems due to discharge by charged metal particles in insulating oil under flow state are examined in this study. The motion characteristics of a charged metal particle in a horizontal transformer oil tract are investigated, and a mechanical model of a charged metal particle under flowing oil and an AC field is proposed. The particle's equations of motion are numerically solved using the fourth-order Runge-Kutta computational algorithm. The trajectory of a spherical iron particle in typical motion state unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…First, considering the oil flow, the force condition of a particle exerted by fluid will be more complicated. Apart from the wall effects and drag force, the flow brings about additional forces such as pressure gradient force, Magnus lift force, Saffman force and so on [99]. These fluid forces need to be re‐examined to understand the migration of particles and oil insulation performance.…”
Section: Discussionmentioning
confidence: 99%
“…First, considering the oil flow, the force condition of a particle exerted by fluid will be more complicated. Apart from the wall effects and drag force, the flow brings about additional forces such as pressure gradient force, Magnus lift force, Saffman force and so on [99]. These fluid forces need to be re‐examined to understand the migration of particles and oil insulation performance.…”
Section: Discussionmentioning
confidence: 99%
“…where s = h/d, G 1 , G 2 are dimensionless, referring to [30], n is the normal vector with respect to the boundary layer near an electrode, and u || is the shear velocity of fluid around the particle. What's more, the particles also receive Basset force F Ba , which can be ignored in this model because of its little effect on particle motion [11].…”
Section: Numerical Modeling Of Particle Motionmentioning
confidence: 99%
“…In recent years, considering this case, our group established a PD test platform for flowing oil contaminated by metallic particles whereby the PD characteristics under different flow rates were preliminarily studied when AC/DC composite voltages were applied. It was demonstrated that PDIVs became higher and the discharge time decreased as the flowing rate increased [11]. Additionally, the discharge was the most severe under AC voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we briefly introduce the model and show its refinements. Other specific details of the model can be acquired from our paper [19]. The particle trajectory was calculated mainly by the motion equation expressed as follows: mpnormaldupnormaldt=bold-italicFnormalG+bold-italicFnormalD+bold-italicFnormalE+bold-italicFotherwhere m p is the particle mass, u p is the particle velocity, F G , F D and F E are the gravitational force, drag force and electric field force, respectively.…”
Section: Simulation Of Metallic Particle Movementmentioning
confidence: 99%
“…The particle trajectory was calculated mainly by the motion equation expressed as follows: mpnormaldupnormaldt=bold-italicFnormalG+bold-italicFnormalD+bold-italicFnormalE+bold-italicFotherwhere m p is the particle mass, u p is the particle velocity, F G , F D and F E are the gravitational force, drag force and electric field force, respectively. In previous studies, a charged particle was idealised simply as a point charge rather than a charged sphere [19]. This simplification would apparently change F E near the electrode when a particle approached an electrode [20, 21].…”
Section: Simulation Of Metallic Particle Movementmentioning
confidence: 99%